Important features of the Greek chariot-races - Anastasiou, Athanasios; Mouratidou, Aikaterini Antigoni (Akademia Wychowania Fizycznego w Poznaniu)
The purpose of this paper is to demonstrate that the date 776 B.C. as the beginning of the ancient Olympic Games should be regarded with extreme caution. Tradition holds that the foot--race was the only event held at Olympia from 776 to 724 B.C. and that chariot racing was introduced at the year 680 B.C., but this is highly unlikely. The archaeological evidence clearly indicates that chariot-races were held at Olympia long before and after the 776 B.C. date. Pindar’s statement that from the very beginning the contests were many, including chariot--races, is closer to the truth. It appears that Pausanias statement is not very convincing, since the Greek nobility of the period was a cavalier one, and it seems unlikely that a hippic event was introduced as late as 680 B.C. The evidence shows that chariot-races were part of the Olympic Games since their early beginnings, were always aristocratic in nature, very exciting and dangerous. This proposition, that is, the existence of chariot--races in the early Greek Games found support from the material evidence not only from Olympia but from many other Greek districts and regions as well.
Keywords: chariot-races; charioteers; aristocratic; dangerous